Enfermeiros da região amazônica brasileira e o acesso à informação na atenção primária à saúde - FERREIRA, Evellyn de Paula Moraes (Universidade Federal do Pará, 2024)
The study aims to analyze the access to information on Primary Health Care (PHC) by nurses from the Brazilian Amazon Region. The research is part of the macro project Nursing Practices in the Context of Primary Care: a national study of mixed methods and its data were collected from November 2019 to August 2021. The participants were 626 nurses, who work in PHC in the Northern Region. For data collection, an electronic questionnaire was used, with closed questions, whose data were stored in the Microsoft Excel program. The chi-square test was used to evaluate differences in the proportion of access to information between the states of the North Region, by which the two states with lower coverage (Amapá and Pará) were compared to each other and then to the others. Also, the chi-square partition test was applied and, for the variables that presented statistical significance, the residue test was used, considering a residual value equal to or greater than 1.96 for p < 0.05. These analyzes were performed using the program bioestatₒ and the resulting data were presented in the form of tables. The study was approved by the Research Ethics Committee (CEP) of the University of Brasília under opinion no. 4.263.831 and CEP of the Federal University of Pará under opinion no: 4.520.687. When comparing the states of the Northern Region with Pará and Amapá, which have lower PHC coverage, the following results: Roraima has a higher proportion of nurses who access information on Primary Health Care by printed means (p = 0.0177); Amazonas (p < 0.0001), Rondônia (p = 0.0049), Roraima (p = 0.0288) and Tocantins (p = 0.0014) have higher proportions of nurses who access information in the workplace; Amazonas nurses access less information published in scientific journals (p = 0.0388); nurses in Roraima have a higher proportion of access to information from specialized books (p = 0.0247); and nurses in Rondônia (p = 0.0373) and Roraima (p = 0.0357) have greater access to information from government sources. The access to information and resources by the nurses of the PHC of the Brazilian Amazon participating in the research, involve a combination of specific training, cooperation with health networks, partnerships with organizations and access to online portals and specialized publications, elements that contribute to the continuous training of nurses and that improve the quality of health care offered in the Brazilian Amazon.